New Charge-Transfer Complexes of Organochalcogenide Compound Based on Aryl Acetamide Group with Quinones: Synthesis, Characterization, Antioxidant, and Computational Study - Attared Fadhel Hassan; Nahed Hazim Al-Haidery; Suhad Rajab Kareem; Sabah Abbas Malik; Shaker Abdel Salem Al-Jadaan; Nuha Hussain Al-Saadawy (Indonesian Journal of Chemistry, 2024)
This study aims to prepare charge transfer complexes derived from organochalcogenide of arylamide derivatives with different quinones. A new charge-transfer complexes have been developed through a direct reaction between (PhNHCOCH2)2Se, (o-CH3PhNHCOCH2)2Se, and (PhCH2NHCOCH2)2E, where E = S, Se, and Te are electron donors and different quinones are electron acceptors. The quinones used in the reaction were 2,3-dichloro-5,6-dicyanobenzoquinones (DDQ), 7,7’,8,8’-tetracyanoquinodimethane, and tetracyanoethane. The electron donors and electron acceptor mol were 1:1, and the reaction was conducted in acetonitrile. Infrared, 1H and 13C-NMR spectroscopic data characterized all complexes. The complexes’ antioxidant activity was evaluated through α,α-diphenyl-β-picrylhydrazyl at 10–0.312 mg/mL. The results showed that all complexes exhibited promising antioxidant activities. Among them, (PhCH2NHCOCH2)2S·DDQ compound had the least IC50 value of 6.725 mg/mL, indicating a potent scavenging property compared to other compounds. The molecular structures of charge-transfer complexes were investigated using hybrid density functional theory (B3LYP) and basis set 3-21G. We obtained geometrical structures' highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) surfaces and energy gaps through geometric optimization. We also investigated the molecular shapes and contours of the prepared compounds through geometrical optimization and compared the HOMO energy of the CT compounds to investigate donor and acceptor properties.